Social Media Recruitment and Online Data Collection: A Beginner's Guide and Best Practices for Accessing Low-Prevalence and Hard-to-Reach Populations - King, David B.; O'Rourke, Norm; DeLongis, Anita (Canadian psychology = Psychologie canadienne, 2014)
One facet of the growing social media phenomenon is the opportunity to directly appeal to prospective research participants. An example of this is Facebook advertising to defined populations. In conjunction with online data collection, social media advertising can simplify and accelerate data collection, and it can do so at greatly reduced costs. Thanks to these contemporary tools, responses can be collected at the same time from participants living in Vancouver, Toronto, and St. John's. In this article, we describe how social media can be used for rapid and cost-effective data collection. Moreover, these methods allow researchers to directly access prospective study participants who may be otherwise difficult to reach (because of their low prevalence, their remote location, or organisational barriers). For illustrative purposes, we review methods from 2 studies: 1 of older adults with bipolar disorder and 1 of Canadian paramedics and their spouses. In both cases, participants clicked sociodemographically targeted Facebook advertisements and were directed to online study questionnaires. Based primarily on these 2 lines of research, we offer recommendations and best practices for researchers interested in utilizing social media for online recruitment and data collection. We contend that in many instances, social media may be the most effective means to recruit participants from low-prevalence and invisible populations. The majority of Canadians, and indeed much more of the world population than was previously accessible, can be reached via social media today. In addition to offering strategies to improve participant communication, we also review the limitations of social media advertising and online research. La possibilité de solliciter directement des sujets potentiels pour la recherche est l'un des avantages du phénomène croissant des médias sociaux. Sur Facebook, la publicité ciblant certains segments de la population en constitue un exemple. Parallèlement à la collecte de données en ligne, la publicité diffusée sur les médias sociaux peut simplifier et accélérer le processus de collecte de données, cela à un coût beaucoup moindre. Grâce à ces outils modernes, il est possible de recevoir simultanément les réponses de répondants habitant à Vancouver, à Toronto et à St. John's. Dans cet article, nous expliquons la façon d'utiliser les médias sociaux pour effectuer une collecte de données rapide, efficace et peu onéreuse. De plus, ces méthodes permettent aux chercheurs de communiquer directement avec des participants aux études prospectives qui seraient difficiles à joindre autrement - en raison d'une faible prévalence, de leur lieu d'habitation dans une région éloignée ou d'obstacles organisationnels. À titre d'information, nous examinons les méthodes employées dans deux études : une consacrée aux adultes âgés présentant un trouble bipolaire, et l'autre consacrée au personnel paramédical canadien et à leurs épouses ou époux. Dans les deux cas, les répondants ont cliqué sur les annonces de Facebook ciblées sur le plan sociodémographique et ont été dirigés vers des questionnaires d'étude. En nous basant principalement sur ces deux domaines de recherche, nous présentons des recommandations et des pratiques exemplaires aux chercheurs souhaitant utiliser les médias sociaux pour effectuer un recrutement et une collecte de données en ligne. Nous estimons que, dans de nombreux cas, les médias sociaux constituent le moyen le plus efficace de recruter des sujets au sein de segments de population à faible prévalence et méconnus. Aujourd'hui, la plupart des Canadiens - et, bien entendu, une plus grande partie de la population mondiale qu'auparavant - peuvent être joints par l'intermédiaire des médias sociaux. En plus de proposer des stratégies pour améliorer la communication avec les répondants, nous étudions les limites de la publicité sur les médias sociaux et celles de la recherche en ligne.